Variability in spectrophotometric pyruvate analyses for predicting onion pungency and nutraceutical value - Beretta, Hebe Vanesa (2017)
Onion pyruvate concentration is used as a predictor of flavor intensity and nutraceutical value. The protocol of Schwimmer and Weston (SW) (1961) is the most widespread methodology for estimating onion pyruvate. Anthon and Barret (AB) (2003) proposed modifications to this procedure. Here, we compared these spectrophotometry-based procedures for pyruvate analysis using a diverse collection of onion cultivars. The SW method always led to over-estimation of pyruvate levels in colored, but not in white onions, by up to 65%. Identification of light-absorbance interfering compounds was performed by spectrophotometry and HPLC analysis. Interference by quercetin and anthocyanins, jointly, accounted for more than 90% of the over-estimation of pyruvate. Pyruvate determinations according to AB significantly reduced absorbance interference from compounds other than pyruvate. This study provides evidence about the mechanistic basis underlying differences between the SW and AB methods for indirect assessment of onion flavor and nutraceutical value.